How Corporate Governance Quality and Carbon Risk Shape Earnings Management: Evidence from Indonesian Consumer Non-Cyclical Companies - Nurul Rezeqiyah; Arum Ardianingsih (Business, Accounting, and Knowledge Journal, 2026)
Earnings management continues to represent a critical challenge because it reduces the credibility of financial reporting and weakens stakeholders' confidence in corporate disclosures. This study investigates the influence of corporate governance quality, carbon risk, corporate social responsibility (CSR), and auditor independence on earnings management among consumer non-cyclical companies listed on the Indonesia Stock Exchange during the 2019–2023 period. A quantitative explanatory approach was employed using secondary data collected from audited annual reports. Firm-year observations were selected through purposive sampling, and the hypotheses were examined using multiple linear regression after all classical assumption tests confirmed the appropriateness of the research model. The findings reveal that higher corporate governance quality and stronger auditor independence significantly constrain earnings management by improving monitoring effectiveness and enhancing the reliability of financial reporting. Conversely, greater carbon risk increases managerial incentives to manipulate reported earnings due to heightened environmental and operational uncertainty. Corporate social responsibility also exhibits a significant relationship with earnings management, indicating that sustainability initiatives influence managerial financial reporting behavior. These findings contribute to the corporate governance and sustainability literature by demonstrating that reporting quality is jointly determined by governance mechanisms, environmental risk exposure, and corporate responsibility practices. The study further offers practical implications for regulators, investors, auditors, and corporate managers in strengthening governance systems and promoting more transparent financial reporting.